INTEGRATION OF 3D MODELING AND VISUALIZATION TECHNOLOGIES INTO THE EDUCATIONAL PROCESS IN GEOGRAPHICAL RESEARCH - Qudratov Shahboz (International Scientific and Current Research Conferences, 2025)
The growing availability of geospatial big data and affordable high-performance graphics hardware has transformed the didactic landscape of geography. Three-dimensional (3D) modeling and advanced visualization environments now enable students to explore terrain morphology, urban morphodynamics and climatic interactions through immersive representations that approximate professional research workflows. The present study investigates how systematic incorporation of 3D geographic information system (GIS) tools, photogrammetric modelling and game-engine visualizations enriches learning outcomes in undergraduate and graduate geography curricula. A quasi-experimental design conducted at Samarkand State University compared cohorts taught with conventional two-dimensional cartography against cohorts exposed to a scaffolded sequence of 3D exercises. Quantitative assessment of spatial reasoning skills, project accuracy and reflective diaries demonstrate significant improvements in conceptual retention and methodological autonomy among the experimental group (p < 0.05). Qualitative analysis of student portfolios indicates heightened motivation and an ability to critically evaluate data quality and model uncertainty. The article discusses pedagogical implications, outlines an implementation roadmap and proposes quality-assurance criteria compatible with Higher Attestation Commission standards.